Cascade of Care for Hepatitis C Virus Infection Within the US Veterans Health Administration - Maier, Marissa M. (Am J Public Health, 2016)
Objectives. We measured the quality of HCV care using a cascade of HCV care model. Methods. We estimated the number of patients diagnosed with chronic HCV, linked to HCV care, treated with HCV antivirals, and having achieved a sustained virologic response (SVR) in the electronic medical record data from the Veterans Health Administration’s Corporate Data Warehouse and the HCV Clinical Case Registry in 2013. Results. Of the estimated 233 898 patients with chronic HCV, 77% (181 168) were diagnosed, 69% (160 794) were linked to HCV care, 17% (39 388) were treated with HCV antivirals, and 7% (15 983) had achieved SVR. Conclusions. This Cascade of HCV Care provides a clinically relevant model to measure the quality of HCV care within a health care system and to compare HCV care across health systems.